Impact assessment of regulatory governance and regulatory policies on port sustainability performance - Roy, Manikant (Nanyang Technological University, 2021)
In the last decades, port devolution has led to port reforms through the involvement of local government and private management in port governance. The involvement of private companies in ports has significantly commercialised the port industry. Therefore, this study reviews port governance and regulatory theories to analyse port governance using the capture theory of regulation. Review and analysis of port governance show that there are three adverse impacts of port reforms in achieving port sustainability performance (PSP). Firstly, economically, port corporations and private terminal operators in some ports have gained monopolistic power. Secondly, environmentally, the rapid growth of port infrastructure and maritime traffic has adverse consequences on the environment. Thirdly, socially, working conditions of employees of ports may not improve or improve insufficiently while port throughput and hence workload increases. These three adverse impacts of port reforms create major hurdles in the path of PSP. Moreover, regulatory agencies may not be able to address these adverse impacts due to potential conflict of interest in the functioning of regulatory agencies such as port authorities (PA) and possibilities of regulatory capture. Therefore, international organisations, governments, non-governmental organisations, and the public are constantly raising significant concerns to achieve PSP. In these scenarios, governments and port regulatory agencies need to intervene to safeguard public interests. Therefore, this study aims to discuss the theoretical foundation of regulatory governance (RG) and regulatory policies (RPs) as a possible solution to deal with the adverse impacts of port reforms and assess the impact of RG and RPs on PSP. Moreover, this study aims to evaluate the significance of transparency and accountability of PA’s governance on stakeholder’s acceptance of economic regulatory policies (ER), environmental regulatory policies (EVR), and social regulatory policies (SR). This study further aims to evaluate the impact of RPs on economic performance, environmental performance, and social performance of ports respectively. Through a questionnaire survey responded by port stakeholders, the study finds that transparency and accountability of PA’s governance positively correlate with stakeholders’ acceptance of ER, EVR, and SR of ports. Incorporating transparency and accountability in a port authority’s governance was found to have positive acceptance on ER, EVR, and SR of ports with estimates value of 0.58, 0.84, and 0.74, respectively. The study also indicates that there is a greater significance of transparency and accountability of a port authority’s governance on EVR and SR with estimates of 0.84 and 0.74 in comparison to ER with an estimate of 0.58. This result indicates that incorporating transparency and accountability in a port authority's governance significantly increases the acceptance of EVR and SR despite the cost of policy implementation. The result further shows that RPs has a positive impact on components of PSP with an estimate of 0.94. Moreover, RPs have a positive impact on economic performance, environmental performance, and social performance of ports with the estimated value of 0.62, 0.76 and 0.80, respectively. The study also finds that RPs have a positive impact not only on environmental performance and social performance of ports but also on economic performance of ports. The positive impact of RPs on economic performance negates the industry perception that RPs have negative impacts on economic performance of ports.